Asuhan Keperawatan Pada Tn. D Dengan Gangguan Sistem Limfatik: Post Operasi Limfadenopati Sinistra Di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Sefila Meilda Naifah; Ahmad Zakiudin (STIKES Columbia Asia Medan, 2026)
Background: Lymphadenopathy is an enlargement of the lymph nodes commonly caused by infection or inflammatory processes, which may lead to pain and risk of postoperative complications. This study aims to provide a comprehensive description of nursing care for a patient following left-sided lymphadenopathy surgery. Method: This case study used a nursing process approach, encompassing data collection through interviews, observation, physical examination, and documentation review of medical records conducted in Mawar 2 Ward at RSUD dr. Soeselo, Tegal Regency. Results: Based on assessment, three primary nursing diagnoses were identified: acute pain, knowledge deficit, and risk of infection. Following standard nursing interventions, pain was reduced, patient knowledge improved, and the wound was maintained without signs of infection. Conclusion: The systematic application of nursing care can help reduce patient complaints and prevent postoperative complications of lymphadenopathy.